Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 4 - Proportions, Percents, and Solving Inequalities - Chapters 1-4 Cumulative Review Problem Set - Page 186: 15



Work Step by Step

We substitute $x=3$ and $y=-6$ in the expression and simplify: $\frac{3x-2y}{2x-3y}$ =$\frac{3(3)-2(-6)}{2(3)-3(-6)}$ =$\frac{9+12}{6+18}$ =$\frac{21}{24}$ =$\frac{7}{8}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.